2012
DOI: 10.1080/10852352.2012.660124
|View full text |Cite
|
Sign up to set email alerts
|

Differential Challenges in Coalition Building Among HIV Prevention Coalitions Targeting Specific Youth Populations

Abstract: Coalitions provide the potential for merging the power, influence, and resources of fragmented individuals and institutions into one collective group that can more effectively focus its efforts on a specific community health issue. Connect to Protect® coalitions devote resources to address the HIV epidemic at a structural level. This research examines differential challenges in coalition processes that may facilitate/hinder coalition building to achieve HIV prevention through structural change. Qualitative int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…Perceived expertise often gives researchers priority in agenda-setting, legitimacy in research activities, and power within the overall partnership (Cherry & Shefner, 2004; Pokorny et al, 2004). Interpersonal, institutional, and larger systemic conflicts may persist as a result of inequitable decision-making processes and access to resources (Afshar, 2005; Bayne-Smith, Mizrahi, & Garcia, 2008; Robles-Schrader, Harper, Purnell, Monarrez, & Ellen, 2012). Arguably, researchers’ perspectives are often privileged and promoted within partnerships.…”
mentioning
confidence: 99%
“…Perceived expertise often gives researchers priority in agenda-setting, legitimacy in research activities, and power within the overall partnership (Cherry & Shefner, 2004; Pokorny et al, 2004). Interpersonal, institutional, and larger systemic conflicts may persist as a result of inequitable decision-making processes and access to resources (Afshar, 2005; Bayne-Smith, Mizrahi, & Garcia, 2008; Robles-Schrader, Harper, Purnell, Monarrez, & Ellen, 2012). Arguably, researchers’ perspectives are often privileged and promoted within partnerships.…”
mentioning
confidence: 99%
“…89S development, implementation, and evaluation of social change interventions (Eng & Blanchard, 2006;Harper, Contreras, Bangi, & Pedraza, 2003;Robles-Schrader et al, 2012;Suarez-Balcazar & Harper, 2003;Ziff et al, 2006). Health-focused coalitions have demonstrated that participatory processes are effective in addressing historical and systemic barriers to health promotion and in designing effective community-determined solutions (Harper et al, 2004;Israel et al, 2010;Lantz, Viruell-Fuentes, Israel, Softley, & Guzman, 2001).…”
mentioning
confidence: 99%
“…Decades of research has illustrated the value and importance of using collaborative processes to address historical injustices (Israel, Schulz, Parker, & Becker, 1998; Schulz, Krieger, & Galea, 2002; Wallerstein & Duran, 2006). The creation of community coalitions allows stakeholders to assess community needs, share their perspectives, and actively shape and participate in the development, implementation, and evaluation of social change interventions (Eng & Blanchard, 2006; Harper, Contreras, Bangi, & Pedraza, 2003; Robles-Schrader et al, 2012; Suarez-Balcazar & Harper, 2003; Ziff et al, 2006). Health-focused coalitions have demonstrated that participatory processes are effective in addressing historical and systemic barriers to health promotion and in designing effective community-determined solutions (Harper et al, 2004; Israel et al, 2010; Lantz, Viruell-Fuentes, Israel, Softley, & Guzman, 2001).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These data underscore the importance of developing interventions that meet and address YGBMTW's HIV/STI prevention needs effectively, including the development of race‐specific cultural messages (Harper, Tyler, Bruce, Graham & Wade, ) and strengths‐based approaches (Reed & Miller, ) when working with young racial/ethnic YGBMTW populations. Thus, consistent with a community organizing framework, program planning efforts must identify the structural and community factors that fuel these disparities, and propose sustainable, high‐impact solutions that are reflective of communities often times underrepresented, marginalized, or stigmatized (Harper, ; Harper et al., ; Miller et al., ; Robles‐Schrader, Harper, Purnell & Monares, ).…”
mentioning
confidence: 99%